Georg Simmel's aesthetics in the young Ortega - Gutiérrez Gutiérrez, Eduardo (Anales del Seminario de Historia de la Filosofía, 2021)
This article consists of an analysis of the influence of the Berlin philosopher Georg Simmel on the initial stages of José Ortega y Gasset's philosophy. In this case, we will focus on the influence that Simmel's aesthetics exerted on the young Ortega for the configuration of a theory of the historical evolution of the arts in which some of the strong theses that would characterize his mature thought are revealed.It should be noted that this article is included within a project of analysis of the relationship of influence between Simmel and Ortega, an influence that covers multiple fields of philosophical and scientific thought, such as epistemology, aesthetics, ontology, sociology, etc., as well as diverse and interesting contents of analysis.The main objective is to demonstrate that under the fundamental ideas of Ortega y Gasset's philosophy of historical and vital reason flows the tension between life and form that is the basis of Simmelian thought.
Keywords: Classicism; Georg Simmel; Art History; Ortega y Gasset; Romanticism